Crop-livestock integration and the physical resilience of a degraded Latosol - José Fausto Guimarães Silva; Wainer Gomes Gonçalves; Kátia Aparecida de Pinho Costa; José Flávio Neto; Marlete Ferreira de Brito; Felipe Carreira da Silva; Eduardo da Costa Severiano (Semina: Ciências Agrárias, 2019)
The degradation of pastures in Brazil is a problem of agronomic and environmental importance because it impairs the productive capacity of the soil and the hydrological cycle. In this context, the integration of agriculture and livestock emerges as a promising practice in recovering degraded soils through aggregation, increasing organic carbon in the soil and breaking compacted layers via the growth of grass roots. This study aimed to evaluate suitable indicators of physical quality in regard to mitigating structural changes of a Latosol cultivated with different species of the genus Brachiaria. We evaluated the grasses Brachiaria brizantha (Xaraés, Piatã, Marandu), Brachiaria decumbens and Brachiaria ruziziensis and adopted fallow and conventional tillage as controls. Soil samples were used to evaluate the parameters total organic carbon, soil aggregation via wet sieving and the least limiting water range (LLWR). Total organic carbon and aggregate stability were not suitable indicators for quantifying soil structural changes, remaining high in the evaluated conservation systems, with a difference observed only in the control with conventional tillage. The LLWR varied among all systems and layers evaluated. Xaraés palisadegrass, followed by the Piatã and Marandu cultivars, stood out in terms of biological soil loosening ability, being similar to the recovery caused by soil tillage. Furthermore, B. decumbens showed intermediate performance, while B. ruziziensis showed activity similar to that in the fallow treatment, indicating limited potential for soil physical recovery.